Intramedullary Spinal Schwannoma: Case Report and Review of Preoperative Magnetic Resonance Imaging Features - T. Ho; K.S. Tai; L.L.Y. Leong (Asian Journal of Surgery, 2006)
Intramedullary schwannomas are rare spinal cord tumours. Correct preoperative diagnosis is essential for proper surgical planning and complete resection. We present a case of cervical intramedullary schwannoma followed by discussion on its preoperative magnetic resonance imaging features and review of the literature.